The evolutionary history of the extinct ratite moa and New Zealand Neogene paleogeography - Bunce, Michael; Worthy, T.; Phillips, M.; Holdaway, R.; Willerslev, E.; Haile, James; Shapiro, B.; Scofield, R.; Drummond, A.; Kamp, P.; Cooper, A. (National Academy of Sciences, 2009)
The ratite moa (Aves: Dinornithiformes) were a speciose group of massive graviportal avian herbivores that dominated the New Zealand (NZ) ecosystem until their extinction !600 years ago. Thephylogeny and evolutionary history of this morphologically diverse order has remained controversial since their initial description in 1839. We synthesize mitochondrial phylogenetic information from 263subfossil moa specimens from across NZ with morphological, ecological, and new geological data to create the first comprehensive phylogeny, taxonomy, and evolutionary timeframe for all of thespecies of an extinct order. We also present an important new geological/paleogeographical model of late Cenozoic NZ, which suggests that terrestrial biota on the North and South Island landmasseswere isolated for most of the past 20–30 Ma. The data reveal that the patterns of genetic diversity within and between differentmoaclades reflect a complex history following a major marine transgression inthe Oligocene, affected by marine barriers, tectonic activity, and glacial cycles. Surprisingly, the remarkable morphological radiation of moa appears to have occurred much more recently than previousearly Miocene (ca. 15 Ma) estimates, and was coincident with the accelerated uplift of the Southern Alps just ca. 5–8.5 Ma. Together with recent fossil evidence, these data suggest that the recentevolutionary history of nearly all of the iconic NZ terrestrial biota occurred principally on just the South Island.